Pendampingan Pembuatan Kompor Energi Alternatif Berbahan Bakar Limbah Serbuk Kayu dan Sekam Padi di Kelurahan TPU Keramat Cereme Taba Lubuklinggau - Yaspin Yolanda; Ahmad Amin; Armi Yuneti (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
Based on the observations we made in the TPU Keramat Cereme Taba Village, which is part of the area in Lubuklinggau City, most of the people make a living as wood craftsmen and farmers often cause problems, namely the increasing number of piles of sawdust and rice husks that have not been handled, then the high gas elpigi because it is difficult to find and the community. The goal is to manufacture energy-efficient stoves fueled by sawdust and rice husk waste as a solution to overcome waste. The method of implementing the activities is in the form of lectures, demonstrations and direct practicums. The implementation time is March to June 2021. The target of this activity is youth and women in the village. Evaluation of the increase in participants' knowledge was carried out by pre- and post-test after socialization. The evaluation of participants' skills was carried out during a direct demonstration of stove making. The results of the PKM implementation showed success because there was an increase in knowledge of around 87.5 percent, namely (a) an increase in participants' knowledge about the usefulness of sawdust and rice husk waste by 89 percent. (b) Increased knowledge during media demonstrations about the efficiency of sawdust and rice husk stoves (KOKADI) compared to Elpigi Gas Stoves by 87 percent. (c) Increased knowledge of KOKADI stove maintenance techniques by 88 percent. And (d) Improving community skills regarding the manufacture of KOKADI stoves by 86 percent. This service activity is classified as successful, with an average increase of more than 70 percent, which is an increase of around 87.5 percent. All participants attended PKM activities starting from the opening, the benefits of sawdust and rice husk waste, simulating the manufacture of KOKADI stoves, and observing directly the process of comparing the efficiency of KOKADI with Elpigi gas stoves (KGE).